Intentional Switching Between Bimanual Coordination Patterns in Older Adults: Is It Mediated by Inhibition Processes? - Temprado, Jean-Jacques; Torre, Marta Maria; Langeard, Antoine; Julien-Vintrou, Marine; Devillers-Réolon, Louise; Sleimen-Malkoun, Rita; Berton, Eric (Frontiers in Aging Neuroscience, 2020)
We investigated age-related decline in inhibition processes on intentional switching between bimanual coordination patterns. Fifteen young (24±2.8 years) and twenty older adults (69±5.3 years) performed Stroop tasks and bimanual coordination tasks. Stroop tasks included neutral, congruent, and incongruent conditions. Bimanual coordination tasks consisted of performing in-phase (IP) and anti-phase (AP) patterns. Participants were requested to switch as quickly as possible from one pattern to the other, resulting in two different switching directions (AP to IP; IP to AP). Mean, and standard deviation (SD) of the Continuous Relative Phase (CRP) were calculated pre- and post-switching for each participant. Total switching time (TST) was measured. The switching phase was also decomposed into Reaction Time (RT) and Reversal Time (REvT). Pearson correlation analyses were performed to test for correlations between: i) SD of RP and RespT in Stroop tasks, and ii) switching times (TST, RT, RevT) and RespT in Stroop task, respectively. In addition, parallel mediation analyses were conducted. Results showed that: i) the AP pattern was less stable than the IP pattern in both young and older adults, ii) coordination patterns were less stable in older adults, iii) RespTs in Stroop task were longer in the incongruent condition, and iv) RespTs were longer in older than in young participants, whatever the condition. In the bimanual coordination task, RT, RevT, and TST increased with age. The stability of the IP pattern was correlated with the response times observed in neutral and congruent conditions, while the stability of the AP pattern was correlated with response time observed in the incongruent condition. Correlation and mediation analyses showed that, in the AP to IP switching direction, reaction time and reversal time were both strongly correlated with response times observed in the incongruent condition of Stroop task. These findings suggest that inhibition processes are involved in switching between bimanual coordination patterns, at least to trigger the early phase of switching. They also suggest that inhibition processes are more involved in switching from AP to IP. Finally, age-related changes in switching times seem to be prominently mediated by alterations of inhibition processes.